An optimized sandwich bumper beam for child occupant head injury prevention - Abdul Aziz, Nuraini; Rafukka, Ibrahim; Arumugam, Manohar (National School of Applied Sciences, Chouaib Doukkali University, 2024)
Child fatalities from motor vehicle crashes are recently being considered as a global problem. Various mitigation systems have been proposed, but are still not optimum. Designing energy absorption vehicle front has been one of the methods used to minimize vehicle deceleration. This in addition to child restraint seat could help minimize child injuries especially to the most sensitive part of human body, the head. Sandwich bumper beam absorbs huge kinetic energy by plastic deformation and lead to reduction of vehicle deceleration and subsequent lower occupant injuries. In this work, optimization was carried out seeking for the optimum design of composite beam thickness ( and foam thickness ( of a sandwich bumper that will minimize Head Injury Criteria ( and ) to child occupant at 48 km/h frontal impact. Sampling design of the bumper and beam thickness applying design of experiment and finite element (FE) crash simulations using LS DYNA was applied to evaluate the three year old (3YO) child model head injury responses. Optimization models were developed which were in turn used in optimization process. The optimization was carried out using polynomial Response Surface Method (RSM) for and . The bumper beam and foam thickness that gives a minimum and of 386.6 and 311.5 respectively are 100 mm with 1 mm . Lastly, the work, suggested the need for employing the relationship that exist between child occupant response and bumper material and thickness in design considerations.